2014
DOI: 10.1108/ijm-05-2013-0109
|View full text |Cite
|
Sign up to set email alerts
|

Graduates’ job satisfaction across domains of study

Abstract: Purpose -The purpose of this paper is to address the problem of job satisfaction determinants of higher education graduates across six selected study domains. Design/methodology/approach -Based on the theoretical considerations, derived from human capital theory and signalling theory, the authors formulate the model explaining job satisfaction as a broad measure of labour market success. Explanatory variables include various socio-demographic characteristics as well as market environment and process of learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…Despite a rapidly growing economy in need of skilled labor, unemployment has been rising among young and better educated people (Wongnaa & Seyram, 2014). On the one hand, the theory of human capital may not be as causal as claimed, which questions the role of higher education in satisfying the immediate needs of companies (Gajderowicz et al., 2014). On the other hand, the rapid expansion of higher education has produced an unparalleled number of highly skilled workers whose employment prospects are gradually becoming more uncertain.…”
Section: Graduates’ Transition To the Labor Marketmentioning
confidence: 99%
“…Despite a rapidly growing economy in need of skilled labor, unemployment has been rising among young and better educated people (Wongnaa & Seyram, 2014). On the one hand, the theory of human capital may not be as causal as claimed, which questions the role of higher education in satisfying the immediate needs of companies (Gajderowicz et al., 2014). On the other hand, the rapid expansion of higher education has produced an unparalleled number of highly skilled workers whose employment prospects are gradually becoming more uncertain.…”
Section: Graduates’ Transition To the Labor Marketmentioning
confidence: 99%
“…In 2014, a team of Polish researchers looked for differences in the determinants of job satisfaction across fields of study using data for several European countries based on data from the Research into Employment and professional Flexibility (REFLEX) and Higher Education as a Generator of Strategic Competences (HEGESCO) projects. Gajderowicz et al (2014) used explanatory variables such as demographic variables, study process characteristics, study programme characteristics, teaching modes, personal attitude, international mobility experience, work experience and current job characteristics to find Labour market success empirical analysis significant drivers of graduate success in the labour market. They found that job satisfaction differs across study domains (for similar studies see also De Santis et al, 2021).…”
Section: Central European Graduates' Researchmentioning
confidence: 99%
“…However, the vertical mismatch is more focused on overeducation issues, instead of undereducation (Sloane, 2007). Overeducation is a situation where an individual works in a job that requires a lower level of education qualification than their actual educational qualification (Garcia-Espejo & Ibáñez, 2006;Rahona-López & Pérez-Esparrells, 2013;Gajderowicz et al, 2014) and vice versa for undereducation. Meanwhile, required education is a situation where the educational qualification matches the education required by employment.…”
Section: Vertical Mismatch and Overeducationmentioning
confidence: 99%